The Quality of Sputum Specimens as a Predictor of Isolated Bacteria From Patients With Lower Respiratory Tract Infections at a Tertiary Referral Hospital, Denpasar, Bali-Indonesia - Budayanti, Nyoman Sri; Suryawan, Kadek; Iswari, Ida Sri; Sukrama, Dewa Made (Frontiers in Medicine, 2019)
Sputum quality is crucial in finding infectious bacteria that will be used to guide definitive antibiotic therapy. Errors in reporting isolated bacteria will affect the rate of patients’ morbidity, mortality, and increase patient care costs. This study aims to find out the relationship between sputum quality and isolated bacteria at a Tertiary Referral Hospital, Denpasar, Bali-Indonesia. The study was conducted for 6 months in the Sanglah Hospital Clinical Microbiology laboratory. There were 726 sputum specimens examined and categorized based on Murray Washington criteria. After Gram examination, all specimens were inoculated on aerobic culture media. We classified 41.4% of poor-quality sputum specimens, and non-pathogenic bacteria were isolated from 70.2% of that specimen dominated by Streptococcus mitis (42.53%). Whereas isolated pathogens were obtained from 54.4% of good-quality sputum specimens dominated by Klebsiella pneumonia (30.86%). Statistical analyses showed that there is a relationship between isolated bacteria and the sputum quality (OR=3.844; p=0.00). Good-quality sputum is 3.8 times more likely to isolate pathogenic bacteria than poor-quality sputum. In the Pearson Chi-Square test, the likelihood of isolating pathogenic bacteria from good-quality specimens was significant too (p=0.00). The results of this study indicate that poor-quality sputum specimens are still found. Therefore, the capacity of good sputum collection must be improved. Supervision of the application of standard sputum culture operational procedures must be more rigorously carried out.